"Turning garbage into luxury": the materiality in practices of the carnival production - Ana Carolina Júlio; César Tureta (BBR: Brazilian Business Review)
This paper analyzes the organization of the carnival production of a samba school. Specifically, we investigate the effort to balance the demand for luxury and the scarcity of resources. To understand these phenomena, we use Schatzki’s epistemology of practice. This is a qualitative research that resorts to participant observation, in-depth interviews and documentary research. The findings revealed that the practice of material reuse is incorporated in the carnival production. We show evidence that the balance between luxury and the scarcity of resources occurs through what we call material understandings, a central element in the creative process. These understandings are produced from the interaction of the actors with a set of material arrangements, through which the creative process takes place. We also emphasize that they can be transformed throughout carnival production, as practitioners seek solutions to emerging problems.